2012
DOI: 10.1007/s12639-012-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Linguatula serrata nymphs in goats slaughtered in Tabriz, Iran

Abstract: During 1 year (April 2009-April 2010, the prevalence of Linguatula serrata (L. serrata) nymphs in liver and mesenteric and mediastinal lymph nodes (MLN) of 740 native goats of different sex and ages were examined in Tabriz, north west of Iran. Initially the organs were macroscopically examined for nymphal stage of L. serrata and then were digested by acid-pepsin method to further investigation. The prevalence rate was obtained 55.27%. The mesenteric lymph nodes (MLN) in 334 (45.13%), the lymph nodes (LN) in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…In the first step of examination, the prevalence of L. serrata infection were detected 24.81% (100/403) (Rezaei et al, 2012;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Kheirabadi et al, 2014), 9-52.5% in sheep (Tavassoli et al, 2007a;Nourollahifard et al, 2011;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Azizi et al, 2015;Kheirabadi et al, 2015), and 14.8-69.1% in cattle (Tajik et al, 2006;Nourollahifard et al, 2010b;Youssefi and Hadizadeh-Moalem, 2010;Rezaei et al, 2011;Youssefi et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the first step of examination, the prevalence of L. serrata infection were detected 24.81% (100/403) (Rezaei et al, 2012;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Kheirabadi et al, 2014), 9-52.5% in sheep (Tavassoli et al, 2007a;Nourollahifard et al, 2011;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Azizi et al, 2015;Kheirabadi et al, 2015), and 14.8-69.1% in cattle (Tajik et al, 2006;Nourollahifard et al, 2010b;Youssefi and Hadizadeh-Moalem, 2010;Rezaei et al, 2011;Youssefi et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Ingestion of L. serrata nymphs can cause halzoun or Marrara syndrome that is characterized by inflammation of the upper respiratory tract, swelling of the submaxillary and cervical lymph nodes, and occasionally abscess formation in the eyes or ears (Yazdani et al, 2014). Previous studies in Iran have reported the prevalence rates of L. serrata infection as 27.8-76.5% in dogs (Meshgi and Asgarian, 2003;Rezaei et al, 2011), 19-68% in goats (Dehkordi et al, 2014;Rezaei et al, 2012;Youssefi et al, 2012), 10.2-52.5% in sheep (Dehkordi et al, 2014;Fard et al, 2011;Tavassoli et al, 2007b;Youssefi et al, 2012), and 14.8-69.1% in cattle (Alborzi et al, 2013;Fard et al, 2010a;Nematollahi et al, 2015;Rezaei et al, 2011;Tajik et al, 2006;Youssefi et al, 2012;Youssefi and Moalem, 2010). In India, infection rates have been reported to be 21% in goats and 19% in cattle (Ravindran et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the possibility of infection in MLNs is higher than other visceral organs (Rezaei et al, 2011;Sadeghi-Dehkordi et al, 2014). In Iran, L. serrata infection rate was reported 19-68% in goats, 10.2-52.5% in sheep and 14.8-69.1% in cattle (Alborzi et al, 2013;Nematollahi et al, 2015;Nourollahi Fard et al, 2010;Nourollahi Fard et al, 2011;Rezaei et al, 2011, Rezaei et al,2012Sadeghi-Dehkordi et al, 2014;Tajik et al, 2006;Tavassoli et al, 2007;Youssefi and Hadizadehmoalem, 2010;Youssefi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Deaths have been reported due to blocked air passages (Yazdani et al, 2014). In the previous researches from Iran, the L. serrata infection was reported in different animals, such as dogs (Rezaei et al, 2011), camels (Haddadzadeh et al, 2009), buffaloes (Alborzi et al, 2013), sheep (Nourollahi Fard et al, 2011), goats (Rezaei et al, 2012), and cattle (Tajik et al, 2006). Also, linguatulosis in humans has recently been reported in Kerman province, Southeastern Iran (Yazdani et al, 2014).…”
Section: Araştırma Makalesimentioning
confidence: 99%